Direct measurement of the mass transport coefficient of water in silica-gel using the zero length column technique. (15th January 2022) - Brandani, Stefano; Mangano, Enzo
Abstract: In all silica-gel adsorption processes driven by low-grade heat, the kinetics of adsorption of water on silica-gel is very important in order to optimize design and becomes an essential factor in ultra-low grade heat applications. A new approach for the determination of the mass transfer coefficient of water in commercial silica-gel is proposed and demonstrated with measurements on a single particle using the zero length column technique. Under equilibrium conditions the methodology offers the key advantage to acquire equilibrium isotherms with thousands of points in less than one day. This allows to obtain the relationship between vapour concentration and equilibrium adsorbed amount through numerical interpolation. At higher flowrates, the system operates under kinetic control therefore allowing the determination of the mass transfer coefficient. The novel approach calculates all the elements needed to obtain the mass transfer coefficient from the measured signals without the need to use a specific model. Adsorption and desorption experiments were carried out at different flowrates and three different temperatures. The kinetic responses can be used to determine an average mass transfer coefficient, which is consistent with literature values, but a complex behaviour is observed with surface diffusion as the main contribution to the transport process.